1999
DOI: 10.1007/s001250051159
|View full text |Cite
|
Sign up to set email alerts
|

Intensity and mechanisms of in vitro xenorecognition of adult pig pancreatic islet cells by CD 4 + and CD 8 + lymphocytes from Type I diabetic or healthy subjects

Abstract: Type I diabetes could be treatable by a graft of pig islets [1]. Rejection of this discordant xenograft remains, however, a major problem. Despite advances in the understanding of hyperacute rejection that have made short-term engraftment of porcine tissue a feasible objective, cell-mediated rejection can occur. This cellular rejection could be a serious problem in the case of islets, which are possibly less susceptible to hyperacute rejection [2,3].In vitro human cellular recognition in the discordant human-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 14 publications
(17 reference statements)
1
17
0
Order By: Relevance
“…Previous studies have shown this to be a strong immune response that is difficult to suppress (5,(32)(33)(34). It is different mechanistically from allograft rejection in that CD8 ϩ T cells are not involved, and more macrophage-mediated destruction occurs at early time points (35,36).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown this to be a strong immune response that is difficult to suppress (5,(32)(33)(34). It is different mechanistically from allograft rejection in that CD8 ϩ T cells are not involved, and more macrophage-mediated destruction occurs at early time points (35,36).…”
Section: Discussionmentioning
confidence: 96%
“…The primers amplified a 7.2 kb fragment from all PERV-A, -B, or -C sequences. 6 (Pharmacia Biotech, Uppsala, Sweden). Thirteen microlitres of cDNA templates were amplified with pol, gag, env-A, env-B or env-C primers in the conditions described above.…”
Section: Methodsmentioning
confidence: 99%
“…The primers used for PCR amplification of PERV sequences or pig mt DNA were synthesised by the Life Tech-During xenograft, there is a risk of transmitting infectious agents from pig to man. The risk of conventional zoonosis led us to isolate islets from specific pathogen-free (SPF) pigs [1,2,3,4,5,6,7,8]. However, there is also a risk of transmitting porcine endogenous retroviruses (PERV) [9,10,11,12].…”
Section: Pcr-derived Monitoring Of Perv Infection and Microchimerism mentioning
confidence: 99%
“…Murray et al demonstrated that islet rejection likely occurs via a CD4+ T cell-directed response, with NK cell and CD8+ T cell-mediated injury of the xenograft not contributing to islet loss [37]. Additionally, a study by Lalain et al [39]. examined the adaptive immune response in vitro to adult porcine islets in type 1 diabetic and healthy human subjects.…”
Section: Adaptive Immune Responsementioning
confidence: 99%
“…examined the adaptive immune response in vitro to adult porcine islets in type 1 diabetic and healthy human subjects. It was shown that the immune response to porcine islet cells involves dominantly CD4+ T cells activated through the indirect pathway, as well as CD8+ T cells activated through the direct pathway [39].…”
Section: Adaptive Immune Responsementioning
confidence: 99%